Cardiovascular comorbidities of rheumatoid arthritis in Taiwanese adults: A retrospective single-center study - Ning-Sheng Lai; Chun-Lung Wang; Ming-Chi Lu; Malcolm Koo (Tzu Chi Medical Journal)
Objective: To evaluate the association between rheumatoid arthritis (RA) and cardiovascular comorbidities, including hyperlipidemia, hypertension, and diabetes, in Taiwanese patients based on the data from medical records. Materials and Methods: A retrospective study was performed using the computerized medical records from a regional hospital located in southern Taiwan. A total of 2293 patients (age range 30–79 years) with a diagnosis of RA (International Classification of Diseases, Ninth Revision, Clinical Modification code 714.0) treated since the opening of the study hospital in July 2000 until February 2013 were included. The RA cases were frequency matched for age and sex with 9172 patients without RA. The associations of RA with hyperlipidemia, hypertension, and diabetes were evaluated using multiple logistic regression analysis. Results: Significant associations between RA and hyperlipidemia (adjusted odds ratio [OR] = 2.05, 95% confidence interval [CI] = 1.77–2.38,P< 0.001) and hypertension (adjusted OR = 2.76, 95% CI = 2.43–3.14,P< 0.001) were observed. However, diabetes was not significantly associated with RA in either male or female patients. Conclusion: Findings from this retrospective medical record study indicated that hyperlipidemia and hypertension were significant cardiovascular comorbidities of RA.